Molluscs (Scottish Historical and Archaeological Internet Reports, 2001)
The most prevalent marine species are common mussels and common cockles, though in low numbers. Terrestrial and freshwater species were dominated by taxa typical of disturbed but shaded habitats associated with stone buildings or rubble.